Huygens Metasurface Holograms with the Modulation of Focal Energy Distribution. Issue 12 (6th April 2018) - Wang, Zhuochao; Ding, Xumin; Zhang, Kuang; Ratni, Badreddine; Burokur, Shah Nawaz; Gu, Xuemai; Wu, Qun
Abstract: Huygens metasurface, an implementation of Huygens principle with metasurface, shows great potential in the manipulation of electromagnetic wave by elaborately designed subwavelength scale metaatoms with full phase coverage and high transmission amplitude. Here, a multiphase hologram with Huygens metasurface is demonstrated in microwave regime, and a novel algorithm method is proposed to modulate energy distribution among focal points. The proof‐of‐concept experiments show superior microwave holographic images with 89% transmittance efficiency, 59% imaging efficiency, and 1.65 root‐mean‐square error of focal intensity ratio. The proposed Huygens metasurface hologram expands the route to microwave applications for holographic technologies, including computer‐generated holograms, antennas, security, and data storage. Abstract : Novel Huygens metasurface holograms and a new method of algorithm for the manipulation of focal intensity distribution in a holographic image are proposed and verified by proof‐of‐concept experiments in the microwave regime. The evaluation parameters are measured as 89% transmittance efficiency, 59% imaging efficiency, and 1.65 root‐mean‐square error, empowering a superior holographic image quality in the microwave band.